Patient acceptability of circulating tumour DNA testing in endometrial cancer follow‐up. (22nd February 2021) - Relton, Anna; Collins, Anna; Guttery, David S.; Gorsia, Diviya N.; McDermott, Hilary J.; Moss, Esther L.
Abstract: Objective: Circulating tumour DNA (ctDNA) is emerging as a potential option to detect disease recurrence in many cancer types, however, ensuring patient acceptability of changing clinical practice and the introduction of new technology is paramount. Methods: Patients enrolled in a non‐intervention cohort study determining the ability of ctDNA to detect recurrent endometrial cancer (EC) were invited to participate in a semi‐structured interview. Analysis was performed by Template Analysis. Results: Eighteen patients were interviewed. A ctDNA blood test was viewed by participants as more physically and psychologically acceptable than clinical examination to monitor for EC recurrence. In particular, participants expressed overwhelming preference for a blood test rather than pelvic examination. Although participants acknowledged that an abnormal ctDNA result could cause anxiety, they expressed a preference to be informed of their results, even if a recurrence was too small to detect radiologically. Explanations for these opinions were a desire for certainty whether their cancer would recur or not, and knowledge would help them be more aware of symptoms that should be reported to their clinician. Conclusions: ctDNA monitoring to identify EC recurrence appears to be acceptable to patients, and for many, it may be preferable to clinical examination.